2017
DOI: 10.1242/jeb.161737
|View full text |Cite
|
Sign up to set email alerts
|

Aversive learning of odor-heat associations in ants

Abstract: Ants have recently emerged as useful models for the study of olfactory learning. In this framework, the development of a protocol for the appetitive conditioning of the maxilla-labium extension response (MaLER) provided the possibility of studying Pavlovian odor-food learning in a controlled environment. Here we extend these studies by introducing the first Pavlovian aversive learning protocol for harnessed ants in the laboratory. We worked with carpenter ants and first determined the capacity of different tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 59 publications
2
10
0
1
Order By: Relevance
“…Moreover, the nature of the neutral stimulus and the valance of the unconditional stimulus can influence learning performance. For example, Desmedt et al (2017) found that Camponotus aethiops retained an association between a negative stimulus (heat) and 1-Hexanol 10 min after exposure, while they failed to retain a similar association to Octanal. Drosophila larvae successfully learn to associate a reward (fructose) with either light or dark, but seem unable to learn to associate punishments (table salt or quinine) with light levels (Gerber et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the nature of the neutral stimulus and the valance of the unconditional stimulus can influence learning performance. For example, Desmedt et al (2017) found that Camponotus aethiops retained an association between a negative stimulus (heat) and 1-Hexanol 10 min after exposure, while they failed to retain a similar association to Octanal. Drosophila larvae successfully learn to associate a reward (fructose) with either light or dark, but seem unable to learn to associate punishments (table salt or quinine) with light levels (Gerber et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Carrillo et al, 2000). Insects are not an exception to this situation: differential conditioning enhances discrimination and decreases the level of generalization between olfactory stimuli in fruit flies (Barth et al, 2014) and carpenter ants (Desmedt et al, 2017;Josens et al, 2009;Perez et al, 2016). In honey bees, a similar phenomenon has been observed in the case of visual discriminations (Avargues-Weber and Giurfa, 2014).…”
Section: Discussionmentioning
confidence: 71%
“…Bees had to learn the discrimination between the CS+ and the CS−. This conditioning form is particularly useful to determine whether individuals can indeed distinguish between two stimuli as it improves discrimination in various species and sensory modalities due to the different outcome of the conditioned stimuli (Avargues-Weber and Giurfa, 2014; Barth et al, 2014;Desmedt et al, 2017;Dyer and Chittka, 2004;Giurfa, 2004;Giurfa et al, 1999;Hanson, 1959;Josens et al, 2009;Perez et al, 2016).…”
Section: Experiments 2: Differential Conditioningmentioning
confidence: 99%
“…For example, in honey bees, sting extension response (SER) conditioning research investigates how restrained bees learn to sting in response to a stimulus associated with shock (Vergoz et al, 2007;Tedjakumala & Guirfa, 2013). Similar work has also been conducted in other Hymenoptera (e.g., Desmedt et al, 2017). Unfortunately, there is not yet analogous work with bumble bees.…”
Section: Introductionmentioning
confidence: 99%